1999
DOI: 10.1074/jbc.274.50.35393
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Phosphatidylinositol Transfer Protein α in NIH3T3 Cells Activates a Phospholipase A

Abstract: In order to investigate the cellular function of the mammalian phosphatidylinositol transfer protein ␣ (PI-TP␣), NIH3T3 fibroblast cells were transfected with the cDNA encoding mouse PI-TP␣. Two stable cell lines, i.e. SPI6 and SPI8, were isolated, which showed a 2-and 3-fold increase, respectively, in the level of PI-TP␣. Overexpression of PI-TP␣ resulted in a decrease in the duration of the cell cycle from 21 h for the wild type Upon equilibrium labeling of the cells with myo-[ 3 H] inositol, the relative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 48 publications
1
39
1
Order By: Relevance
“…These proteins are involved in phospholipids degradation, phospholipids transport, as well as in dynamic cytoskeleton changes and in function of Golgi system (Wirtz, 1991(Wirtz, , 1997Snoek et al, 1999). It seems that the decrease of PI-TP protein level may be one of the important factors that lead to disturbing of phospholipids signaling and also may be involved in neurodegeneration of CNS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins are involved in phospholipids degradation, phospholipids transport, as well as in dynamic cytoskeleton changes and in function of Golgi system (Wirtz, 1991(Wirtz, , 1997Snoek et al, 1999). It seems that the decrease of PI-TP protein level may be one of the important factors that lead to disturbing of phospholipids signaling and also may be involved in neurodegeneration of CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the cellular functions of PI-TP are not only connected with phospholipid transfer per se from its site of synthesis in the endoplasmic reticulum to the other membranes but also with other important cell functions as vesicle transport, dynamics of cytoskeleton proteins, and PI metabolism (Thomas et al, 1993b;Liscovitch and Cantley, 1995;Monaco et al, 1998;Snoek et al, 1999). PI-TP is an essential for agonist stimulated synthesis of polyphosphoinositide (Thomas et al, 1993b;Kauffmann-Zeh et al, 1995;Kearns et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As yet, it is not at all clear how PI-TPa interacts with PI 4-kinase for PI to become available for phosphorylation or with phospholipase A 2 for PI to become hydrolyzed Snoek et al, 1999). In the open structure of PI-TPa the hydroxyl groups at positions 3, 4 and 5 of the phosphorylinositol moiety are located in front of the hydrophilic hole of the lipid-binding channel (Schouten et al, 2002).…”
Section: D-structure and Phospholipid Specificity Pi-tpamentioning
confidence: 99%
“…Both isoforms act as carriers of PI and phosphatidylcholine (PC) between membranes in vitro, yet PI-TPb can also transfer sphingomyelin (SPM) (Van Paridon et al, 1987b;De Vries et al, 1995). At this point it is still questionable whether these proteins actually transfer these phospholipids between membranes within cells or whether they interact directly with enzymes like PI 4-kinases and PI-specific phospholipase A 2 thereby providing these enzymes with substrates Snoek et al, 1999). In analogy with observations in yeast it has also been proposed that by binding either PI, PC or SPM, PI-TPs act as regulators of phospholipid metabolism at distinct sites in the cell thereby fulfilling the roles of biosensors (McGee et al, 1994;Bankaitis, 2002).…”
Section: Introductionmentioning
confidence: 99%